Peran Pandangan Dunia dan Emosi Positif terhadap Kepribadian Multikultural - Yusuf Fajar; Thomas Dicky Hastjarjo (Gadjah Mada Journal of Psychology (GamaJoP), 2017)
The world is now becoming more interconnected so that people need the ability to adapt cross-culturally to deal with it. Multicultural personality is one of the concepts of cultural adaptability. This study aims to examine empirically the role of the world view and positive emotions on the multicultural personality of the students. The hypothesis of this study was the world view and positive emotions would be able to predict student multicultural personality. The subjects of the study were 132 undergraduates and master students of UGM. Three scales, multicultural personality scales, world view scales, and positive emotion scales were distributed to the subjects. Data analysis was done by multiple regression. The results showed that the world view and positive emotions together play a role in predicting student multicultural personality with R = 0,313, F = 7,008 and p = 0,001 (p <0,01). The world view and positive emotions together made a contribution of 9.8% in multicultural personality. This study showed that from these two variables only positive emotions predicted the multicultural personality.